Here's the question you clicked on:
dotdotdog
Find an equation that has -5 and 8 as solutions. Write your equation in standard form. For example, 4 and -3 are solutions to x^2-x-12=0.
(x+5)(x-8) = 0 x = -5 is a solution (makes the first factor zero) x = 8 is a solution (makes the second factor zero)
now expand it to standard form
Another way to do this: Find the sum of the solutions. That is 3. Find the product of the solutions. That is - 40. Now, reverse the sign of the sum of the solutions. That is - 3. Then, your equation is \[x^{2} - 3x -40=0\]